Analysis of Creative Character Needs and Effective Communication for Aceh Vocational School Students - Hamid, Arhamni; Supian, Zahari; Anwar*, Anwar; Idris, Saifullah; Yusmina, Erra; Tanjong, Akbari (Universitas Syiah Kuala, 2024)
Effective communication and creative thinking are soft skills that are very necessary in the 21st century. Character is a set of traits which means personality and morals. This research aims to describe the analysis of needs for designing instruments for assessing effective communication and creative thinking for Aceh vocational school students in carrying out assessments of effective communication and creative thinking. Data was obtained from a questionnaire of 65 Aceh Vocational School students. The sample used was 65 Aceh vocational school students. Data was collected through a questionnaire distributed to the entire sample. Data were analyzed using the social sciences statistical package version 25.0 for frequency, percentage, mean and standard deviation. The research results show the need to study effective communication and creative thinking as a reference in preparing students to enter the world of work and industry. This is done because so far there has been no assessment of effective communication and creative thinking because there are no instruments, so it cannot be concluded whether students who have completed vocational education so far have done well or not in meeting government and industry expectations. The character of effective communication and creative thinking is an important and necessary consideration in the industrial world known as atitut. On this basis, it can be concluded that it is necessary to design an instrument to assess the character of effective communication and creative thinking